2010
DOI: 10.1504/ijbra.2010.032119
|View full text |Cite
|
Sign up to set email alerts
|

Strategies for enhanced annotation of a microarray probe set

Abstract: We aim to determine the biological relevance of genes identified through microarray-mediated transcriptional profiling of Xenopus sensory organs and brain. Difficulties with genetic data analysis arise because of limitations in probe set annotation and the lack of a universal gene nomenclature. To overcome these impediments, we used sequence based and semantic linking methods in combination with computational approaches to augment probe set annotation on a commercially available microarray. Our curation effort… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2012
2012
2012
2012

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 17 publications
(19 reference statements)
0
4
0
Order By: Relevance
“…Powers et al [55] implemented manual and large-scale computational approaches to expand annotation of the X. laevis GeneChip® Xl-PSIDs by linkage to ion channel genes, HGNC symbols identified via UniGene cluster IDs, or Swiss-Prot proteins from multiple species (human, mouse, fly and worm). Similar manual approaches were used to link X. laevis GeneChip® Xl-PSIDs to five categories of genes with expected inner ear function: (1) inner ear tissue genes, IET; (2) genes implicated in human deafness, DF; (3) genes for ion channels, IC, (4) genes for ion transport, IT; and (5) genes for transcription factors, pTF (see Additional file 2).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Powers et al [55] implemented manual and large-scale computational approaches to expand annotation of the X. laevis GeneChip® Xl-PSIDs by linkage to ion channel genes, HGNC symbols identified via UniGene cluster IDs, or Swiss-Prot proteins from multiple species (human, mouse, fly and worm). Similar manual approaches were used to link X. laevis GeneChip® Xl-PSIDs to five categories of genes with expected inner ear function: (1) inner ear tissue genes, IET; (2) genes implicated in human deafness, DF; (3) genes for ion channels, IC, (4) genes for ion transport, IT; and (5) genes for transcription factors, pTF (see Additional file 2).…”
Section: Methodsmentioning
confidence: 99%
“…Consequently, the IT category of 370 genes was represented by 180 IT/Xl-PSIDs. Manual curation efforts as described in Powers et al [55] ensured that all IT/Xl-PSIDs identified by keyword query of the X. laevis GeneChip® annotation file were linked to ion transport in primary literature or other online databases. Several ion transport genes were found to be represented by multiple Xl-PSIDs on the X. laevis GeneChip®.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations